Pseudomonas aeruginosa Modulates the Antiviral Response of Bronchial Epithelial Cells - Sörensen, Michael; Kantorek, Julia; Byrnes, Lauren; Boutin, Sébastien; Mall, Marcus A.; Lasitschka, Felix; Zabeck, Heike; Nguyen, Dao; Dalpke, Alexander H. (Frontiers in Immunology, 2020)
Cystic fibrosis (CF) patients frequently acquire Pseudomonas aeruginosa infections that have been associated with a bad prognosis and an increased rate of pulmonary exacerbations. Respiratory viruses can cause exacerbations in chronic pulmonary diseases including COPD or asthma and have been suggested to contribute to exacerbations also in CF. In this study we investigated a possible link between P. aeruginosa infection and susceptibility to respiratory viruses. We show that P. aeruginosa is able to block the antiviral response of airway epithelial cells thereby promoting virus infection and spread. Mechanistically, P. aeruginosa secretes the protease AprA in a LasR dependent manner, which is able of directly degrading epithelial-derived IFNλ resulting in inhibition of IFN signaling. In addition, we correlate the virus infection status of CF patients with the ability of patients’ P. aeruginosa isolates to degrade IFNλ. In line with this, the infection status of CF patients correlated significantly with the amount of respiratory viruses in sputum. Our data suggest that the interplay between P. aeruginosa and respiratory virus infections might partially explain the association of increased rates of pulmonary exacerbations and P. aeruginosa infections in CF patients.